(3GdaJGhis - (3CMeO Hf jMji Hf GdeQJVj Hf eaVd Hf efUhQ GdMSfj, GdegOj dOjf Gddg,J (B840 (3g` s ((3Ydi Hf SYjO Hf HGRd GdMGJei GdRjOi s)
(3ChdgG (B:s
(3gPg LedI eSGFd SFd YfgG GdEeGe GdegOi cJGH GdWgGQI (B: (3bhdg ai GdCRgGQ eG NQL ef SHjdi Pi Oe s
(3BNQgG (B:s
(3hcPdc ChUi LejY ef JaVd ef GdeSdejf HPdc ai MjGJi hHYO haGJi Je GdcJGH HMeO Gddg GdYRjR GdhgGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3hgj ELGHI GdEeGe deG SCdg Yfg Gdabjg LeGd GdOjf Ydi Hf eMeO Hf CHj GdbGSe GdfMhis
(3HQSe Gdabjg UdGM GdOjf Hf Ydi eMeO GdePMLJis
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B269 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B206s
Keywords: (3GdJUha hGdBOGH GdTQYjIs